Valuasi Ekonomi Dan Potensi Pengembangan Objek Wisata Hutan Mangrove Kampung Nelayan Sejahtera Kelurahan Sumber Jaya Kota Bengkulu - Andriansyah, Faizal; Susatya, Agus; Wiryono, Wiryono; Brata, Bieng; Yurike, Yurike (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2023)
This study aims to determine the economic value of mangrove forest tourism objects in the Prosperous Nelayan Village, Sumber Jaya Village, Kampung Melayu Subdistrict Baai Island, Bengkulu City through economic instruments, namely the Travel Cost Method (TCM) and Willingness to Pay (WTP) along with the variables that influence it and to determine the potential for development based on visitor perceptions. The number of respondents in this study were 50 people. Estimation of economic value is based on the Travel Cost Method, while the factors that influence Willingness to Pay are analyzed using multiple linear regression. Furthermore, the potential for tourism object development is studied descriptively based on the respondents' perceptions. The results showed that the economic value of the mangrove forest tourist attraction Kampung Nelayan Sejahtera based on the total travel costs of 50 respondents during 2 weeks of observation was Rp.5,088,000. The factors that influence the Willingness to Pay for the Mangrove Forest tour of Kampung Nelayan Sejahtera are the total cost of the trip, the age of the respondent, and income. Total travel costs and age have a negative effect on Willingness to Pay, while income has a positive effect on Willingness to Pay. Potential developments that can be carried out are (1) development of all potential natural resources in the Kampung Sejahtera Mangrove Forest such as natural mangrove forest views, biodiversity and community friendliness and culture by building cooperation between the community and all competent parties, (2) Packaging the offered tourist objects with a tourism promotion package to attract visitors from outside the City of Bengkulu, and (3) increasing the construction of tourist facilities, facilities and infrastructure that are urgently needed by tourists/visitors and making improvements to existing infrastructure facilities. having damaged. Keywords : Economic value, travel cost method, willingness to pay